Plant-based meat alternatives for culinary products of restaurant consumption - Shcherbakova, Sofiia; Tyshchenko (Usatiuk), Olena; Tsyrulnikova, Vita (My University, 2023)
The article deals with f meat alternatives out of plant proteins of high nutrition and biological value for culinary products of restaurant establishments. У статті розглядаються альтернативи м’яса з рослинних білків високої харчової та біологічної цінності для кулінарної продукції закладів ресторанного господарства.
Keywords: plant-based meat alternatives; рослинні альтернативи м’ясу; culinary products; кулінарна продукція; restaurant establishments; заклади ресторанного господарства; sustainable consumption; відповідальне споживання; кафедра готельно-ресторанної справи